Certificación Internacional ACI - Inspector especial de obras de concreto - Centro de Transferencia Tecnológica, LanammeUCR (2024)
Certificar a los participantes para la inspección de obras de concreto bajo el protocolo de certificación internacional del ACI (American Concrete Institute) “Concrete Construction Special Inspector”. Se guiará al estudiante en el aprendizaje de los siguientes contenidos: ACI Concrete Terminology, ACI 117 Specification for Tolerances for Concrete Construction and Materials, ACI 213R, Guide for Structural Lightweight-Aggregate Concrete, ACI 301, Specifications for Structural Concrete, ACI 302.1R, Guide to Concrete Floor and Slab Construction, ACI 304R, Guide for Measuring, Mixing, Transporting, and Placing Concrete, ACI 304.2R, Placing Concrete by Pumping Methods, ACI 305R, Guide to Hot Weather Concreting, ACI 306R, Guide to Cold Weather Concreting, ACI 308R, Guide to Curing Concrete, ACI 309R, Guide for Consolidation of Concrete, ACI 318, Building Code Requirements for Structural Concrete, ACI 347R, Guide to Formwork for Concrete, ACI SP-2, Manual of Concrete Inspection, International Code Council (ICC), 2015 International Building Code (IBC), CRSI Manual of Standard Practice.